2010
DOI: 10.1161/hypertensionaha.109.139964
|View full text |Cite
|
Sign up to set email alerts
|

Wave Reflection and Arterial Stiffness in the Prediction of 15-Year All-Cause and Cardiovascular Mortalities

Abstract: Abstract-The value of increased arterial wave reflection, usually assessed by the transit time-dependent augmentation index and augmented pressure (Pa), in the prediction of cardiovascular events may have been underestimated. We investigated whether the transit time-independent measures of reflected wave magnitude predict cardiovascular outcomes independent of arterial stiffness indexed by carotid-femoral pulse wave velocity. A total of 1272 participants (47% women; mean age: 52Ϯ13 years; range: 30 to 79 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
286
4
12

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 319 publications
(318 citation statements)
references
References 41 publications
(45 reference statements)
16
286
4
12
Order By: Relevance
“…Most of these studies have performed only one PWV measurement as it is not otherwise stated. 1,3,[17][18][19][20][21][22][23][24][25][26][27][28] One study reported that one PWV measurement was performed 29 and two studies 30,31 referred that two and three PWV measurements were performed, respectively, and an average value was then calculated. Thus, based on the results of this study, a substantial variation (and 'bias') in the determined CVR and the calculated statistical measures may exist, which depends on the number of PWV measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies have performed only one PWV measurement as it is not otherwise stated. 1,3,[17][18][19][20][21][22][23][24][25][26][27][28] One study reported that one PWV measurement was performed 29 and two studies 30,31 referred that two and three PWV measurements were performed, respectively, and an average value was then calculated. Thus, based on the results of this study, a substantial variation (and 'bias') in the determined CVR and the calculated statistical measures may exist, which depends on the number of PWV measurements.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 However, concerns have been raised as to whether AIx is a reliable measurement of vascular compliance in the elderly 5,6 due to the curvilinear association between AIx and age. 6,7 Interestingly, findings have been contradictory regarding AIx as predictor of CVD where AIx has been associated with increased risk of CVD in highrisk populations 8,9 and in men, 10,11 while its use as a predictor in women 12,13 and in the general population is less certain. 13,14 The association between AIx and traditional CVD risk factors has been analysed in several studies with different methodology and various findings.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Interestingly, findings have been contradictory regarding AIx as predictor of CVD where AIx has been associated with increased risk of CVD in highrisk populations 8,9 and in men, 10,11 while its use as a predictor in women 12,13 and in the general population is less certain. 13,14 The association between AIx and traditional CVD risk factors has been analysed in several studies with different methodology and various findings. [15][16][17][18] Recently, a large study of subjects from the general population reported that associations between AIx and CVD risk factors are dependant of age, and that age had a larger influence on AIx than traditional CVD risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] In addition, the aortic stiffness assessed by invasive methods is also a powerful and independent risk factor for recurrent acute coronary events in patients with coronary artery disease (CAD), including stable angina pectoris (SAP). 12 Hence, we hypothesized that the arterial stiffness assessed by CAVI in ACS patients would be significantly higher than that in SAP patients.…”
Section: Introductionmentioning
confidence: 99%